(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
Baby-dumping is one of the most inhumane acts that is on the rise in Malaysia. News about such incidents is prevalent in the mass media, resulting in a cabinet decision being made that baby-dumping cases should be investigated as homicide and attempted murder in order to curb the number of incidents. This article aims at examining whether the legal framework concerning punishment and prevention are adequate to address this matter. It is found that offenders can be charged under the Penal Code and Child Act of 2001 for any offences regarding the life of a person such as murder, attempted murder, or any act causing death and injury. The Shariah Criminal Offences Act, which is applicable for such offences as close proximity, illegitimate sexual intercourse, public indecency and so on, is also adequate to curb the issue of baby-dumping. However, efforts to inform the public of these must be stepped up. Keywords: abandoned babies, baby-dumping, murder, punishment, prevention, shariah law, civil law